Management of cyst and root knot nematodes: a chemical ecology perspective - Torto, B.; Cortada Gonzales, L.; Murungi, L.K.; Haukeland, Solveig; Coyne, Danny L. (American Chemical Society, 2018)
Plant parasitic nematode infection of crops can be highly detrimental to agricultural production. Since the discovery that plant roots release chemicals that attract the infective stage of plant parasitic nematodes some 80 years ago, significant progress in identifying the signaling molecules has occurred only relatively recently. Here, we review the literature on chemical ecological studies of two major plant parasitic nematode groups: root knot nematodes in the genus Meloidogyne and cyst nematodes in the genus Globodera because of the negative impact their parasitism has on farming systems in Africa. We then highlight perspectives for future directions for their management.